Information and multimedia product in higher education - Kunanets, Natalya; Malynovskyi, Ostap (Видавництво Львівської політехніки, 2012)
The report considers the benefits and effectiveness of information displaying by multimedia technology and the ability to fill its information content by different types of information.
Keywords: multimedia; information; interactivity